Optimal Spatial Taxation: Are Big Cities Too Small? - Jan Eeckhout; Nezih Guner (Institute for the Study of Labor (IZA), 2015)
We analyze the role of optimal income taxation across different local labor markets. Should labor in large cities be taxed differently than in small cities? We find that a planner who needs to raise revenue and is constrained by free mobility of labor across cities does not choose equal taxes for cities of different sizes. The optimal tax schedule is location specific and tax differences between large and small cities depend on the level of government spending and on the concentration of housing wealth. Our estimates for the US imply higher marginal rates in big cities, but lower than what is observed. Simulating the US economy under the optimal tax schedule, there are large effects on population mobility: the fraction of population in the 5 largest cities grows by 8.0% with 3.5% of the country-wide population moving to bigger cities. The welfare gains however are smaller. Aggregate consumption goes up by 1.53%. This is due to the fact that much of the output gains are spent on the increased costs of housing construction in bigger cities. Aggregate housing consumption goes down by 1.75%.
Keywords: H21; J61; R12; R13; 330; misallocation; taxation; population mobility; city size; general equilibrium